The Object database handbook how to select implement, and use object-oriented database - Barry, Douglas K. (John Wiley & Sons, 1996)
The first complete, hands-on guide to choosing, implementing, and managing the right object-oriented database for your organization If you are responsible for selecting and implementing an object-oriented database in your organization, you need a tool to help you evaluate your options and make the right selection. And now here it is: The Object Database Handbook-the first complete, hands-on guide for anyone planning a move to object-oriented database technology. Doug Barry, "Databases" columnist with Object Magazine, provides you with a rational, systematic approach to selecting, implementing, and managing the object-oriented database products best suited to your company's unique computing needs. The book covers all the bases, providing clear, step-by-step guidance on how to: * Match your organization's computing needs against available products * Form a selection team * Implement your database solutions so they work right the first time * Prototype your system * Design or convert data to the new database * Rework an existing relational model into an object model Also, the book provides dozens of valuable checklists that make it easy to identify your needs and match them with the right choices. And several full-scale case studies are developed throughout the book that help you arrive quickly at a practical understanding of the concepts discussed.